COMPARATIVE ANALYSIS OF AN EMPLOYMENT CONTRACT IN KAZAKHSTAN AND THE EEU’S STATES (Journal of actual problems of jurisprudence, 2020)
The comprehensive expansion of economic ties, mutually beneficial socio-political and cultural cooperation together with the common historical development allowed the countries of the post-Soviet space to pay serious attention to the possibilities of integration partnership. The formation of the Eurasian Economic Community on the basis of the Commonwealth of Independent States was the first significant step towards the creation of a powerful economic bloc of the Eurasian continent. The subsequent unification of customs borders in the format of the Customs Union and the creation of the Single Economic Space of Russia, Kazakhstan and Belarus have only confirmed the growing prospects for economic and social rapprochement between these countries. Creation of united labor market on the territory of Eurasian economic Union leads to approximation of the labor laws of the Union’s states. That kind of approximation aims to make cooperation and functioning of the newborn union more effective. The problem concerned the development of the directions and approaches of formation of the uniform labor legislation, among which are the institutes of an employment contract. The article deals with the concept of an employment contract in the labor legislation of the countries and reveals its species and generic characteristics. Comparative analysis of terminology of labor contract of the EEU’s countries, as well as of individual European Union countries was carried out. Key words: employment contract, labor relations, Eurasian economic Union, harmonization.